Effect of hydrogen bonds and π⋯π interactions on the crystallization of phenyl-perfluorophenyl amides: understanding the self-organization of a cocrystal. Issue 29 (8th July 2022) - Pagliari, Anderson B.; Meyer, Alexandre R.; Solner, Vanessa B.; Rosa, Jéssica M. L.; Hörner, Manfredo; Bonacorso, Helio G.; Zanatta, Nilo; Martins, Marcos A. P.
Abstract : Crystallization mechanisms were proposed to investigate hydrogen bond and aromatic donor–acceptor interactions in a series of phenyl–perfluorophenyl amides. The modulation of NH⋯OC bonds and aryl complementarity drove a new cocrystal growth. Abstract : A series of N -arylbenzamides containing amide groups and phenyl–perfluorinated rings were used as the smallest molecules to investigate the direct influence of hydrogen bonds and aromatic donor–acceptor complementarity in the solid state. N -Phenylbenzamide and pentafluoro- N -(perfluorophenyl)benzamide were investigated in self-assembly as well as in cocrystal form. Moreover, the respective mixed phenyl–perfluorinated compounds were used in this study. Supramolecular cluster demarcation was used, and crystallization mechanisms were proposed based on the hierarchy of stabilization energies in one-, two-, or three-dimensional growth processes (1D, 2D, or 3D, respectively). At the molecular level, effects such as torsion, planes, and intramolecular interactions showed significant changes compared to the optimized structures, evidencing the supramolecular influence. When considering the supramolecular environment, crystallization mechanisms of the self-assembly of phenyl–phenyl amide offer a 2D → 3D process, whereas the other compounds were classified in a 1D (chains) → 2D (layers) → 3D stepwise process. The interchain links were driven by C–H⋯π interactions in the self-assembly and π⋯π interactions in the mixed compounds and cocrystal packing. QTAIM analysis evidences the importance and contribution of the strong NH⋯OC hydrogen bond of all crystals. MEP plots highlight the complementarity between amide sites and aromatic rings, helping to understand the cocrystal formation. Lastly, a comparison of the NH⋯OC bond strength of the cocrystal obtained (−11 kcal mol −1 ) with those of similar cocrystals linked by amide bonds deposited in the CSD showed the highest value of the presented cocrystal. These findings will be helpful in the modulation and design of new molecular solids.